Planar molds for UV micro-casting of polymeric micro-devices - Wang, Jane Lu (2009)
UV roller embossing is a promising roll-to-roll fabrication technique which has great potential for mass fabrication of polymeric micro-patterns for micro-fluidic devices. For the preparation for the development of a mold with features directed created onto the roller cylindrical drum, planar molds with two kinds of substrates were first developed and compared. Suitable substrate surface conditions and optimum parameters in photolithography processes were studied through carefully designed experiments. By measuring the contact angle and calculating the surface energy for normal copper cladding substrates and micro-etched copper cladding substrates, higher adhesive energy and thus better developed mold feature were predicted for micro-etched copper cladding substrates. By comparison, replicas from etched substrate molds developed with surface of energy 67.2mJ/ cm2 shows the best structural features with rigid and straight lines, sharp angles and vertical side walls. This further verified the prediction from surface energy calculation. To ensure uniform and to optimize development, UV intensity inside UV Flood was measured for 5 positions with 10 UV lamp height levels. With these measurements, it is recommended to cure roller mold only along its longitudinal axis and a UV light guiding mechanism should be designed to avoid UV affecting other out-of-plane.